Utilisation of Cryopreserved Gametes in Cancer Patients who Underwent Fertility Preservation - Devika Gunasheela; N. Ashwini; Yoshita Saneja; D Deepthi (Journal of Human Reproductive Sciences)
Background: Cancer treatments such as chemotherapy and radiotherapy often compromise fertility by damaging gonadal function, creating a critical need for fertility preservation options. Despite advancements in fertility preservation techniques, there is a significant lack of research focused on their application in Asian cancer patients and their utilisation remains underexplored in this population. Aim: This study aims to evaluate the utilisation rates and outcomes of cryopreserved gametes in cancer patients who underwent fertility preservation before their cancer treatment. Settings and Design: This retrospective study was conducted at our hospital from January 2003 to May 2023. It investigated the utilisation of cryopreserved gametes in 557 male patients aged 15–50 years and 39 female patients aged 15–40 years who opted for fertility preservation before chemotherapy or radiotherapy. Materials and Methods: Data were retrospectively collected, including patient demographics and fertility preservation outcomes. Various fertility preservation methods were employed based on patient suitability and availability. Participants were surveyed to identify reasons for non-utilisation of cryopreserved gametes. All data were collected and analysed following institutional ethical guidelines. Statistical Analysis Used: Descriptive statistics were used to calculate utilisation rates and report clinical pregnancy and live birth rates. Reasons for non-usage were categorised into mortality, spontaneous pregnancies, financial constraints and social factors. Results: Out of 596 participants, only 11 utilised their cryopreserved gametes, yielding a utilisation rate of 1.8%. Among those who used their gametes, clinical pregnancy rates were 66.66% for males and 50% for females, with live birth rates of 33.33% for males and 50% for females. Non-usage was primarily due to mortality, spontaneous pregnancies, financial constraints and social issues. Conclusion: The utilisation rate of cryopreserved gametes was low at 1.8%. Challenges such as mortality, financial constraints and social factors highlight the need for improved counselling and a refined approach to fertility preservation, ensuring services better align with patients’ future needs.